The pathway of neutrophil extracellular traps towards atherosclerosis and thrombosis. (September 2019) - Moschonas, Iraklis C.; Tselepis, Alexandros D.
Abstract: Neutrophil extracellular traps (NETs) are web-like extrusions of genetic material, which are released upon neutrophil activation. NETs consist of a chromatin substructure, onto which a vast array of proteins with various properties is dispersed. NETs production was initially described as an unrecognized defense mechanism of neutrophils, due to their ability to entrap and possibly eliminate a wide range of pathogens. Nevertheless, growing evidence suggests that NETs are implicated in a multitude of pathophysiological conditions, such as autoimmunity, cancer, diabetes mellitus and Alzheimer's disease. Importantly, NETs may also play a decisive role in atherosclerosis and thrombosis. In this context, it has been demonstrated that NETs are present in atherosclerotic lesions of both humans and animal models and are implicated in various mechanisms leading to atherogenesis. Among others, NETs induce oxidative stress and oxidize high-density lipoprotein particles, thus reducing their beneficial cholesterol efflux capacity. NETs also induce endothelial cell dysfunction and apoptosis and promote the generation of anti-double-stranded-DNA autoantibodies. NETs may also play a prothrombotic role, since they form a fibrin-like base for platelet adhesion, activation and aggregation. Furthermore, NETs promote the accumulation of prothrombotic molecules, like von Willebrand factor and fibrinogen, thus significantly contributing to thrombus formation. Notably, there is vast data linking NETs to arterial and venous thrombosis in animal models, as well as in humans. Future large-scale studies should incorporate NETs and their individual components as disease markers, as well as potential therapeutic targets, to reduce atherosclerosis and to prevent thrombosis. Highlights: NETs exist in atherosclerotic lesions of both humans and animal models. NETs contribute to atherosclerosis, as well as to arterial and venous thrombosis. The proatherogenic and prothrombotic activities of NETs are expressed through various mechanisms.